Tailoring Chlorthalidone Aqueous Solubility by Cocrystallization: Stability and Dissolution Behavior of a Novel Chlorthalidone-Caffeine Cocrystal - Christian Rodríguez-Ruiz; Pedro Montes-Tolentino; Jorge Guillermo Domínguez-Chávez; Hugo Morales-Rojas; Herbert Höpfl; Dea Herrera-Ruiz (MDPI AG, 2022)
A cocrystal of the antihypertensive drug chlorthalidone (CTD) with caffeine (CAF) was obtained (CTD-CAF) by the slurry method, for which a 2:1 stoichiometric ratio was found by powder and single-crystal X-ray diffraction analysis. Cocrystal CTD-CAF showed a supramolecular organization in which CAF molecules are embedded in channels of a 3D network of CTD molecules. The advantage of the cocrystal in comparison to CTD is reflected in a threefold solubility increase and in the dose/solubility ratios, which diminished from near-unit values for D0D to 0.29 for D0CC. Furthermore, dissolution experiments under non-sink conditions showed improved performance of CTD-CAF compared with pure CTD. Subsequent studies showed that CTD-CAF cocrystals transform to CTD form I where CTD precipitation inhibition could be achieved in the presence of pre-dissolved polymer HPMC 80-120 cPs, maintaining supersaturation drug concentrations for at least 180 min. Finally, dissolution experiments under sink conditions unveiled that the CTD-CAF cocrystal induced, in pH-independent manner, faster and more complete CTD dissolution when compared to commercial tablets of CTD. Due to the stability and dissolution behavior of the novel CTD-CAF cocrystal, it could be used to develop solid dosage forms using a lower CTD dose to obtain the same therapeutic response and fewer adverse effects.